2023
DOI: 10.1101/2023.02.07.527364
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cardiomyocyte-fibroblast interaction regulates ferroptosis and fibrosis after myocardial injury

Abstract: Neonatal mouse hearts have transient renewal capacity which is lost in juvenile and adult hearts. After myocardial infarction (MI) in neonatal hearts, an initial loss of cardiomyocytes occurs but it is unclear through which type of regulated cell death (RCD). In the current studies, we induced MI in neonatal and juvenile mouse hearts, and show that ischemic cardiomyocytes primarily undergo ferroptosis, a non-apoptotic and iron-dependent form of RCD. We demonstrate that cardiac fibroblasts (CFs) protect cardiom… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Our previous study has found that the co-culture of pancreatic stellate cells and pancreatic cancer cells after PITX2 knockdown inhibited tumor cell growth. Recently, studies have shown a close association between PITX2 and ferroptosis, with PITX2 regulating ferroptosis-related proteins such as GPX4 and LPCAT3 11 . Based on the above ndings, there is an urgent need to elucidate whether PITX2 affects pancreatic cancer by regulating ferroptosis and to understand the signi cance of this regulation on the development of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study has found that the co-culture of pancreatic stellate cells and pancreatic cancer cells after PITX2 knockdown inhibited tumor cell growth. Recently, studies have shown a close association between PITX2 and ferroptosis, with PITX2 regulating ferroptosis-related proteins such as GPX4 and LPCAT3 11 . Based on the above ndings, there is an urgent need to elucidate whether PITX2 affects pancreatic cancer by regulating ferroptosis and to understand the signi cance of this regulation on the development of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%